NK Cell Subtypes as Regulators of Autoimmune Liver Disease - Guohui Jiao; Bangmao Wang (Gastroenterology Research and Practice)
As major components of innate immunity, NK cells not only exert cell-mediated cytotoxicity to destroy tumors or infected cells, but also act to regulate the functions of other cells in the immune system by secreting cytokines and chemokines. Thus, NK cells provide surveillance in the early defense against viruses, intracellular bacteria, and cancer cells. However, the effecter function of NK cells must be exquisitely controlled to prevent inadvertent attack against normal “self” cells. In an organ such as the liver, where the distinction between immunotolerance and immune defense against routinely processed pathogens is critical, the plethora of NK cells has a unique role in the maintenance of homeostasis. Once self-tolerance is broken, autoimmune liver disease resulted. NK cells act as a “two-edged weapon” and even play opposite roles with both regulatory and inducer activities in the hepatic environment. That is, NK cells act not only to produce inflammatory cytokines and chemokines, but also to alter the proliferation and activation of associated lymphocytes. However, the precise regulatory mechanisms at work in autoimmune liver diseases remain to be identified. In this review, we focus on recent research with NK cells and their potential role in the development of autoimmune liver disease.